Recent California tree mortality portends future increase in drought-driven forest die-off. (11th December 2020) - Madakumbura, Gavin D; Goulden, Michael L; Hall, Alex; Fu, Rong; Moritz, Max A; Koven, Charles D; Kueppers, Lara M; Norlen, Carl A; Randerson, James T
Abstract: Vegetation tolerance to drought depends on an array of site-specific environmental and plant physiological factors. This tolerance is poorly understood for many forest types despite its importance for predicting and managing vegetation stress. We analyzed the relationships between precipitation variability and forest die-off in California's Sierra Nevada and introduce a new measure of drought tolerance that emphasizes plant access to subsurface moisture buffers. We applied this metric to California's severe 2012–2015 drought, and show that it predicted the patterns of tree mortality. We then examined future climate scenarios, and found that the probability of droughts that lead to widespread die-off increases threefold by the end of the 21st century. Our analysis shows that tree mortality in the Sierra Nevada will likely accelerate in the coming decades and that forests in the Central and Northern Sierra Nevada that largely escaped mortality in 2012–2015 are vulnerable to die-off.